Philosophy of Divination - Obi, Augustine C. (Uche, 2008)
Situates African divination in relation to divination worldwide. African divination seeks “double” rather than “single” causality, based on a psychology that presupposes not only a soul but also a “double” that can operate in the world of the supernatural.